RASA KEPEMILIKAN: PENERAPAN KONSEP 'HOME' DI PANTI ASUHAN - Pratama, Muhammad Bayu; Ginting, Salmina Wati (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Orphanages are responsible child protection institutions that safeguard children's rights and act as substitutes for parents. The problem lies in the proliferation of illegal and unfit orphanages. This study investigates various strategies and approaches used in providing inclusive caregiving environments aimed at creating a place where children feel comfortable. By examining the implementation of the "home" concept in orphanage settings, this journal highlights the importance of improving emotional well-being and meeting the unique needs of each child. The "Home" concept in orphanage design aims to create an environment that resembles a real home for the children residing there. This can be achieved through architectural designs that prioritize functional and ergonomic spaces, the use of warm colors, and adequate lighting. The selection of furniture and interior decorations also plays a crucial role in creating a comfortable and personal atmosphere. By implementing the "home" concept in orphanage design, it is expected that children living there can experience a sense of comfort, warmth, and security similar to being in their own homes. This concept not only creates an optimal environment for the growth and development of children but also fosters strong emotional bonds between children and their surroundings.